Antidiabetogenic impact of Bitter Melon (Momordica charantia) and Black Cumin (Nigella sativa) on alloxan induced diabetic rabbit model (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The present study was undertaken to investigate the antidiabetic effect of the bitter melon and black cumin on alloxan induced diabetes in experimental rabbits. At 2 to 3 months of age, rabbits were assigned into five groups (A, B, C, D and E) and rabbits were included each group. Group A was kept as control, Group B was treated with alloxan intramuscularly at a dose of 75mg /kg body weight, Group C was treated with bitter melon at a dose of 150gm/kg body weight orally, Group D was treated with black cumin at a dose of 250mg/kg body weight orally, Group E was treated with combined at previous dose. After acclimatization, diabetes was induced in four groups of rabbits (B, C, D and E) by administering alloxan injection. There was significant (p